FULFILLMENT OF WAGE RIGHTS FOR FEMALE WORKERS: at PT. Oro Kopi, Aceh Tengah - Rizki, Ayuni; Syuib, M.; Afrian Mustaqim, Riza (Universitas Islam Negeri Ar-Raniry, 2026)
This study examines the mechanism of the right to wages of permanent female workers in PT. Oro Kopi Aceh Tengah is based on Law Number 11 of 2020 concerning Job Creation. This processing sector is one of the important sectors in rural areas, women workers play a vital role in the dry coffee production process, especially in PT. Copper Sound. The main focus of this research is the implementation of a wage payment mechanism for permanent female workers involved in dry coffee processing. By using qualitative methods and empirical juridical approaches that combine literature review and primary data collection through interviews, observations, and field documentation. The results of the study show that PT. Oro Kopi has implemented a wage payment system in accordance with the Provinsial Minimum Wage (UMP) standards and applicable laws and regulations. However, there is still a need to increase the knowledge of women workers regarding their rights in the world of work so that they can fight for it and be optimally maintained. This research emphasizes the importance of the active role of companies and governments in overseeing and improving legal protection to ensure gender equality and sustainable welfare improvement for women workers while supporting social justice and regional economic development.